Infliximab and etanercept have distinct actions but similar effects on cytokine profiles in rheumatoid arthritis. Issue 2 (October 2015) - Takeshita, Masaru; Suzuki, Katsuya; Kikuchi, Jun; Izumi, Keisuke; Kurasawa, Takahiko; Yoshimoto, Keiko; Amano, Koichi; Takeuchi, Tsutomu
Highlights We compared serum cytokines in RA patients treated by infliximab and etanercept. Serum IL-6 is decreased by etanercept and infliximab treatment to the same degree. Serum IFNγ and TNFβ are increased by infliximab treatment. IFNγ increase is a distinctive feature of the inefficacy of infliximab treatment.